Eksplorasi Penggunaan Media Digital dalam Pelatihan Fonologi pada Anak Disleksia: Studi Kualitatif - Rihasya Addina Putriwita; Roy Romey Daulas Mangunsong; Dodiet Aditya Setyawan (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Dyslexia is a learning disability that affects a child’s reading ability, particularly in the phonological domain. The use of digital applications such as Bookbot Indonesia offers an alternative approach to phonological training. However, the user experience in its implementation still needs to be examined. Objectives: This study aimed to explore the experiences, perceptions, and significance of implementing digital app-based phonology training in improving the reading skills of children with dyslexia. Methods: A qualitative approach with a phenomenological design involving 7 participants, including children with dyslexia, parents, and teachers at Mojosongo State Elementary School V. Data were collected through semi-structured in-depth interviews and passive observation, and then analyzed using thematic analysis. Results: The study findings indicate that using the Bookbot Indonesia app provides a more interactive learning experience and increases children’s engagement in reading practice. Participants also reported improvements in their ability to recognize sounds and letters. However, several challenges were identified, such as distractions from device use, difficulty understanding instructions, and limited supervision during app use. Conclusion: These findings suggest that digital app-based phonology training has the potential to improve reading skills in children with dyslexia when implemented consistently and accompanied by appropriate support. Optimizing the app’s features and support strategies is necessary to enhance the effectiveness and sustainability of the intervention. Keywords: Digital Applications, Dyslexia, Phonological Training, Reading Ability, Qualitative Research.